Children's Sensitivity to Cost and Reward in Decision Making across Distinct Domains of Probability, Effort, and Delay. (31st August 2017) - Gatzke‐Kopp, Lisa M.; Ram, Nilam; Lydon‐Staley, David M.; DuPuis, David
Abstract: Many behavioral paradigms used to study individuals' decision‐making tendencies do not capture the decision components that contribute to behavioral outcomes, such as differentiating decisions driven toward a reward from decisions driven away from a cost. This study tested a novel decision‐making task in a sample of 403 children (age 9 years) enrolled in an ongoing longitudinal study. The task consisted of three blocks representing distinct cost domains (delay, probability, and effort), wherein children were presented with a deck of cards, each of which consisted of a reward and a cost. Children elected whether to accept or skip the card at each trial. Reward–cost pairs were selected by using an adaptive algorithm to strategically sample the decision space in the fewest number of trials. Using person‐specific regression models, decision preferences were quantified for each cost domain with respect to general tolerance (intercept), as well as parameters estimating the effect of incremental increases in reward or cost on the probability of accepting a card. Results support the relative independence of decision‐making tendencies across cost domains, with moderate correlations observed between tolerance for delay and effort. Specific decision parameters showed unique associations with cognitive and behavioral measures including executive function, academic motivation, anxiety, and hyperactivity. Evidence indicates that sensitivity to reward is an important factor in incentivizing decisions to work harder or wait longer. Dissociating the relative contributions of reward and cost sensitivity in multiple domains may facilitate the identification of heterogeneity in suboptimal decision making. Copyright © 2017 John Wiley & Sons, Ltd.